Development of a vitrification method for preserving human myoblast cell sheets for myocardial regeneration therapy - Ohkawara, Hirotatsu (BMC Biotechnol, 2018)
BACKGROUND: Tissue-engineered cardiac constructs have potential in the functional recovery of heart failure; however, the preservation of these constructs is crucial for the development and widespread application of this treatment. We hypothesized that tissue-engineered skeletal myoblast (SMB) constructs may be preserved by vitrification to conserve biological function and structure. RESULTS: Scaffold-free cardiac cell-sheet constructs were prepared from SMBs and immersed in a vitrification solution containing ethylene glycol, sucrose, and carboxyl poly-l-lysine. The cell sheet was wrapped in a thin film and frozen rapidly above liquid nitrogen to achieve vitrification (vitrification group, n = 8); fresh, untreated SMB sheets (fresh group, n = 8) were used as the control. The cryopreserved SMB sheets were thawed at 2 days, 1 week, 1 month, and 3 months after cryopreservation for assessment. Thawed, cryopreserved SMB sheets were transplanted into rat hearts in a myocardial infarction nude rat model, and their effects on cardiac function were evaluated. Cell viability in the cardiac constructs of the vitrification group was comparable to that of the fresh group, independent of the period of cryopreservation (p > 0.05). The structures of the cell-sheet constructs, including cell-cell junctions such as desmosomes, extracellular matrix, and cell membranes, were maintained in the vitrification group for 3 months. The expression of cytokine genes and extracellular matrix proteins (fibronectin, collagen I, N-cadherin, and integrin α5) showed similar levels in the vitrification and fresh groups. Moreover, in an in vivo experiment, the ejection fraction was significantly improved in animals treated with the fresh or cryopreserved constructs as compared to that in the sham-treated group (p < 0.05). CONCLUSIONS: Overall, these results show that the vitrification method proposed here preserves the functionality and structure of scaffold-free cardiac cell-sheet constructs using human SMBs after thawing, suggesting the potential clinical application of this method in cell-sheet therapy.